A demographic study of patients with behavioral and neurodevelopmental disorders among children in East India - Khawash, Papiya; Chatterjee, Anindita; Adrita , Adrita (Indian Journal of Child Health, 2021)
Background: The prevalence of behavioral and neurodevelopmental disorders of children in India is changing according to recent data, as more young children with these problems are now being identified. Aim: Our study aims to assess the emerging patterns of these disorders in patients attending an urban child guidance clinic in Kolkata. Method: A retrospective analysis of the demographic data of patients attending the clinic over the period of 1 year (April 2018–March 2019) was performed. Results: A significant 55.6% of the total 651 patients in our study were children with autism spectrum disorder (ASD). Children <5 years of age constituted a significant percentage (55.3%) of patients attending the clinic and boys were in significantly larger numbers (74.8%) compared to girls (25.2%). About 52.3% of the children came from Kolkata, 35.4% from other districts of West Bengal, 5.4% from other East Indian states, and 6.9% from the neighboring country Bangladesh. Conclusion: ASD, a developmental disability of public health importance affecting both child and family, has been identified in a significantly large number of children in our study. This may be attributed to increased community awareness resulting in earlier identification/referral of cases; although an actual rise in incidence is also a possibility. The male bias noted in the study is ascribed to a significantly larger number of boys with ASD, behavioral issues, attention deficit hyperactivity disorder, learning disabilities, and intellectual impairment.